2013
DOI: 10.1128/aac.01255-13
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Ethambutol with Human Organic Cation Transporters of the SLC22 Family Indicates Potential for Drug-Drug Interactions during Antituberculosis Therapy

Abstract: bAccording to the 2012 WHO global tuberculosis (TB) report (http://apps.who.int/iris/bitstream/10665/75938/1/9789241564502 _eng.pdf), the death rate for tuberculosis was over 1.4 million patients in 2011, with ϳ9 million new cases diagnosed. Moreover, the frequency of comorbidity with human immunodeficiency virus (HIV) and with diabetes is on the rise, increasing the risk of these patients for experiencing drug-drug interactions (DDIs) due to polypharmacy. Ethambutol is considered a first-line antituberculosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 44 publications
3
24
0
1
Order By: Relevance
“…For the OCTs and OATs, we simply calculated the drug-drug interaction index using the equation C max /IC 50 , where C max indicates the maximum concentration and C max,u indicates the maximum unbound concentration of the inhibitor present in the systemic circulation (27,33,(39)(40)(41).…”
Section: Methodsmentioning
confidence: 99%
“…For the OCTs and OATs, we simply calculated the drug-drug interaction index using the equation C max /IC 50 , where C max indicates the maximum concentration and C max,u indicates the maximum unbound concentration of the inhibitor present in the systemic circulation (27,33,(39)(40)(41).…”
Section: Methodsmentioning
confidence: 99%
“…Using an estimated EMB concentration of 67 mM in the portal system after oral dosing, DDI index analysis indicated a rank order of DDI potencies on hOCT1 as enterocyte (0.6) = hepatocyte (0.6) . proximal tubule cell (0.2), all above the 0.1 threshold value (Pan et al, 2013). These values are indicative of high potential for EMBmediated DDIs on hOCT1 affecting disposition and clearance.…”
Section: Drug Metabolism Within the Brain Changes Drug Response Inmentioning
confidence: 95%
“…Treatment of multidrug-resistant tuberculosis (TB; estimated to be 3.7% of new cases and 20% of previously treated cases) includes EMB to reduce the emergence of isoniazid-or rifampinresistant mycobacteria (http://apps.who.int/iris/bitstream/10665/75938/ 1/9789241564502_eng.pdf). In vitro characterization demonstrated that EMB inhibits hOCT1-, hOCT2-, and hOCT3-mediated transport (Pan et al, 2013). Using an estimated EMB concentration of 67 mM in the portal system after oral dosing, DDI index analysis indicated a rank order of DDI potencies on hOCT1 as enterocyte (0.6) = hepatocyte (0.6) .…”
Section: Drug Metabolism Within the Brain Changes Drug Response Inmentioning
confidence: 99%
See 2 more Smart Citations